Enhanced degradation of resin in crude oil-contaminated soil by Bacillus subtilis and Pseudomonas aeruginosa using surfactants - Zhixin Niu; Pengyu Guo; Zhiyun Wang; Ziyao Wang; Taiyu Su (Royal Society Open Science)
Crude oil inevitably pollutes soil and water during extraction, transport and use. The long-term persistence of resin and asphaltene in the environment poses a threat to ecosystems and human health. The removal of heavy components such as resin is the key to the complete remediation of oil-contaminated soil. Bioremediation, a technology that has been demonstrated to be both environmentally friendly and cost-effective, has attracted significant attention among the oil pollution remediation technologies. In this study, two bacteria, Bacillus subtilis and Pseudomonas aeruginosa, isolated from soil contaminated with crude oil, were used to investigate the biodegradation of resin in soil. Surfactants, including Tween-80 (TW-80), octadecyltrimethylammonium chloride (ODAC) and sodium dodecylbenzenesulfonate (SDBS), were supplemented to evaluate the effects of surfactant type and concentration on resin degradation. The results showed that total petroleum hydrocarbon content generally decreased in all treatment groups over time, and surfactant addition was effective in supporting bacterial population. In the single surfactant treatments, overall, Pseudomonas degraded resin more effectively than Bacillus. At the same concentration, SDBS promoted resin degradation more effectively than TW-80 and ODAC at different time points (at the 42nd day: Bacillus, 11.8–19.1 g kg−1; Pseudomonas, 10.7–14.6 g kg−1). In the surfactant complex treatment, the combination of ODAC × SDBS resulted in a significant enhancement of the degradation of resin in the soil. However, the presence of TW-80 inhibited the effect of the other surfactants retarding the degradation of resin. This study demonstrated that the combined use of surfactants and degrading bacteria can promote the degradation of heavy fractions in crude oil present in soil. Nevertheless, further exploration is required into the response between surfactants and pollutants and microorganisms as well as the mechanisms of their interaction.